Vladyslav Elijovych Lyantse (in honour of the 100th anniversary of birth) - O.G. Storozh; G.I. Chuyko; T.S. Kudryk; Ya.V. Mykytyuk; N.S. Sushchyk (Математичні Студії, 2021)
Some pages of biography and main scientific achievements of professor Wladyslaw Elijowich Lyantse, a famous mathematician, are presented.